Big-five personality traits and depression: chain mediation of self-efficacy and walking - Han Cai; Han Cai; Hongtao Song; Hongtao Song; Yating Yang; Yating Yang; Zihe Xiao; Zihe Xiao; Xianlong Zhang; Xianlong Zhang; Feng Jiang; Feng Jiang; et al. (Frontiers in Psychiatry)
BackgroundDepression is a major global public health concern, with research indicating a correlation between personality traits and depression. This study aimed to explore the potential mediating roles of self-efficacy and walking in the relationship between personality traits and depression among Chinese residents.MethodsA cross-sectional questionnaire survey was conducted from July 10 to September 15, 2021, involving 11,031 Chinese residents across 23 provinces, 5 autonomous regions, and 4 municipalities Participants provided data on demographics, personality traits (using the Ten-Item Personality Inventory), self-efficacy (using the New General Self-Efficacy Scale), chronic disease self-management (using the Chronic Disease Self-Management Study Measures), and depression (using the Patient Health Questionnaire-9). After screening, data from 8,499 participants were analyzed. Sequential mediation models were employed, with the Big Five personality traits as predictors, depression as the outcome, and self-efficacy and walking as the mediators.ResultsExtraversion, agreeableness, conscientiousness, and emotional stability were negatively correlated with depression, with self-efficacy and walking as positive mediators in these relationships. Conversely, openness was positively associated with depression, and the self-efficacy-walking chain did not mediate this relationship but rather masked the effect of openness on depression.ConclusionsOur findings suggest that self-efficacy and walking are significant mediators in the relationship between personality traits and depression, potentially mitigating the risk of depressive episodes.